Respuesta :
Need to divide both sides of the equations by -4 and it’s going to give you this m+6=2. Then move the constant to the right-hand side and change its sign and it’s going to give you this m=2-6. And then calculate the difference and then it’s going to give you this m=-4.
Answer:
Answer is m=-4
Step-by-step explanation:
[tex] - 4(m + 6) = - 8 \\ multiply \: by \: - 4 \\ - 4m - 24 = - 8 \\ - 4m = 24 - 8 \\ - 4m = 16 \\ therefore \: m \: = - 4[/tex]
HAVE A NICE DAY!
THANKS FOR GIVING ME THE OPPORTUNITY TO ANSWER YOUR QUESTION.